Environmental impact, durability performance, and interfacial transition zone of iron ore tailings utilized as dam concrete aggregates. (10th April 2021) - Lv, Xingdong; Lin, Yuqiang; Chen, Xia; Shi, Yan; Liang, Renqiang; Wang, Rongkai; Peng, Ziling
Abstract: This paper discusses the utilization of iron ore tailing aggregates (IOTA) as a replacement for normal aggregates (NA) in dam concrete for hydraulic engineering applications. The durability performance of concrete prepared using IOTA and NA, including resistance to chloride-ion permeability, sulfate corrosion resistance, and abrasion-erosion resistance, are investigated in this study. Based on it, the interfacial transition zone (ITZ) characteristics of IOTA and NA samples are examined by scanning electron microscopy with energy dispersive spectroscopy (SEM-EDS) and microscopic nanoindentation. Besides, the economic and environmental evaluations of the IOTA utilization in real hydraulic engineering are proposed. The results show the concrete prepared with IOTA has more superior durability than NA. The abrasion resistance of concrete prepared with IOTA is higher than that of the NA sample by 1.32–2.90 h m 2 /kg. Since the IOTA raw rock has higher compressive strength, lower saturated-surface-dry (SSD) water absorption, and angular shape, the concrete prepared with IOTA has more superior ITZ characteristics and durability performance than NA. Significant economic and environmental benefits of the utilization of IOTA in hydraulic engineering are obtained. The investments into the IOTA utilization in two practical hydraulic engineering applications can save 8.98 × 10 6 USD. It can also reduce the occupied land space, CO2 emission, and water consumption by 151 900 m 2, 8157.0 t, and 942 000 m 3 . The relative reductions of CO2 emission and water consumption, as compared to NA, are 15.7 and 27.4%. Highlights: The ITZ characteristics are examined by SEM-EDS and microscopic nanoindentation. The utilization of IOTA has significant economic and environmental benefits over NA. The concrete prepared by IOTA have better durability performance than NA. The combination of IOTA and cement matrix is more stable and has better ITZ characteristics than NA.